Coping and Adapting to a Changing Climate: Concepts, Issues and Challenges - Hurd, Brian H (Annals of Arid Zone, 2016)
The prospect of climatic changes introduces significant challenges to many vulnerable communities. How these communities choose to prepare depends much on their specific sensitivities, economies, and adaptive capacities. This paper presents an overview of key concepts that underlie the consideration and design of effective climate change adaptation strategies, including issues of the scope of adaptation activities, reactive versus anticipatory adaptation, vulnerability assessment, and adaptation timing. Examples include those related to water resources with a focus on issues relating to the uncertainties involved in designing appropriate climate-wise strategies. Key words: Climate change, adaptation, coping strategies, vulnerability.